COMPARATIVE LEAF ANATOMY AND MICROMORPHOLOGY OF ASYSTASIA GANGETICA T.ANDERSON SUBSP. MICRANTHA (NEES) ENSERMU AND RHINACANTHUS NASUTUS (L.) KURZ (JUSTICIINAE, ACANTHACEAE) FROM PENINSULAR MALAYSIA - Che Nurul Aini Che Amri; Siti Maisarah Zakaria; Rozilawati Shahari; Aidatul Aifa Binti Mohd Tajudin; Noraini Talip; Mohamad Ruzi Abdul Rahman; Nordahlia Abdullah Siam (BRIN Publishing (Penerbit BRIN), 2023)
Acanthaceae family has been used traditionally for medicinal purposes, especially amongst the native communities in Peninsular Malaysia. Nowadays, many taxonomists have difficulties in the identification of the Acanthaceae species due to its morphological similarities and when there is an incomplete part of plants obtained from the field sampling. But until now, there is no comprehensive study that has been documented especially on the Acanthaceae family, specifically for A. gangetica subsp. micrantha and R. nasutus. To avoid incorrect species identification, a systematic study that involved the leaf anatomy and micromorphology parts is being used for the identification and classification of plants in the Acanthaceae. Therefore, the main objective of this present study is to identify the leaf anatomical and micromorphological characteristics that can be used in plant identification and for supportive data in plant classification. The leaf anatomical and micromorphological studies that are conducted on species studied involve several procedures such as cross-section using a sliding microtome, and observation under a light microscope and scanning electron microscope. The anatomical and micromorphological characteristics observed that have been used to identify each species studied include patterns of petiole and midrib vascular bundles, leaf margin, leaf lamina, presence of cuticular striae, and the presence of trichomes. The results of this study showed that the cystolith cells can be found only in midrib of A. gangetica subsp. micrantha while it also recorded in petiole, midrib, and the leaf lamina of R. nasutus. Observation under the light microscope revealed nine types of trichomes in R. nasutus meanwhile seven trichomes were recorded in A. gangetica subsp. micrantha. Other than that, the present of cuticular striae only recorded at the abaxial epidermis of A. gangetica subsp. micrantha. In conclusion, results showed that anatomical and micromorphological characteristics have taxonomic significance that can be used in the identification and classification, especially at the species level